2021
DOI: 10.1002/jbm.b.34913
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of encrustation and physicochemical properties of poly(lactide‐glycolide) Papaverine hydrochloride coating on ureteral double‐J stents after long‐term flow of artificial urine

Abstract: Implantation of ureteral stents is associated with inconvenience for the patient, which is related to the natural ability of the ureter to contract. The most frequently used solution is the systemic administration of a diastolic drug, which has a relaxing effect on smooth muscle cells and decreases inconvenience. Current interdisciplinary research aimed at reducing the complications after the implantation of ureteral stents used in the treatment of upper urinary tracts with regard to infection, initiation of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Soon afterwards, they investigated the impact of artificial urine on the physical and chemical properties of PLGA+PAP-coated stent tubes, building upon the foundation of previous studies on the stent tubes ( Antonowicz et al, 2022 ). The study showed that applying PAP coating increased surface hydrophilicity, which could make stent implantation easier.…”
Section: Future Clinical Applications Of Busmentioning
confidence: 99%
“…Soon afterwards, they investigated the impact of artificial urine on the physical and chemical properties of PLGA+PAP-coated stent tubes, building upon the foundation of previous studies on the stent tubes ( Antonowicz et al, 2022 ). The study showed that applying PAP coating increased surface hydrophilicity, which could make stent implantation easier.…”
Section: Future Clinical Applications Of Busmentioning
confidence: 99%
“…[ 1 ] At present, the most common USs are made of hydrophobic polyurethane or silicone polymers. [ 2 ] Reportedly, over 1.5 million USs are used worldwide every year, but more than 80% of patients normally suffer from the stent‐associated complications of bacterial infection and encrustation. [ 3 ] In the clinic, biofilm formation caused by the adhesion of urinary proteins, crystals and bacteria on the hydrophobic US surface is the main underlying cause of urinary tract infections (UTIs) and encrustation.…”
Section: Introductionmentioning
confidence: 99%
“…20 However, the ends of this type of ureteral stent have a relatively large degree of curling, which causes patient discomfort and can easily cause kidney or bladder irritation. 21,22 Antonowicz et al 23 examined the impact of a biodegradable coating, containing an active diastolic substance, on the physical and chemical properties of ureteral stents used in the treatment of the upper urinary tract. The surface of PU double-J stents was coated with poly(lactide-glycolide) 85/15 loaded with diastolic papaverine hydrochloride, which has a relaxing effect on smooth muscle cells and decreases the patient's discomfort due to the stent implantation.…”
Section: Introductionmentioning
confidence: 99%